2019
DOI: 10.3389/fevo.2019.00112
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Introductions of Mycobacterium tuberculosis Lineage 2–Beijing Into Africa Over Centuries

Abstract: The Lineage 2-Beijing (L2-Beijing) sub-lineage of Mycobacterium tuberculosis has received much attention due to its high virulence, fast disease progression, and association with antibiotic resistance. Despite several reports of the recent emergence of L2-Beijing in Africa, no study has investigated the evolutionary history of this sub-lineage on the continent. In this study, we used whole genome sequences of 781 L2 clinical strains from 14 geographical regions globally distributed to investigate the origins a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 70 publications
7
38
0
Order By: Relevance
“…Our findings would suggest the frequency of Lineage 2–Beijing in Tanzania, like in most parts of the continent except for South Africa [39,40] to be relatively low, despite the long-standing African-Asian contacts [40]. Evidence from recent studies show that Lineage 2–Beijing was only recently introduced into Africa [13,41].…”
Section: Discussionmentioning
confidence: 73%
“…Our findings would suggest the frequency of Lineage 2–Beijing in Tanzania, like in most parts of the continent except for South Africa [39,40] to be relatively low, despite the long-standing African-Asian contacts [40]. Evidence from recent studies show that Lineage 2–Beijing was only recently introduced into Africa [13,41].…”
Section: Discussionmentioning
confidence: 73%
“…Since the publication of the MTB reference genome [6], whole genome sequence (WGS) data of MTB strains is becoming available at increasing speed, and especially in the last five years, studies using large WGS data sets allowed for precise estimates of the MTB genetic diversity and of the molecular clock rate. Phylogenetic analyses with a molecular clock have been used to estimate the timing of the introduction of MTB clades to particular geographic regions, the divergence time of the MTB lineages, and the age of the most recent common ancestor (MRCA) of the MTB complex [713]. Clock models, together with phylodynamic models in a Bayesian setting have been used to characterize tuberculosis epidemics by determining the time at which outbreaks began and ended [1418], establishing the time of origin and spread of drug resistant clades [11, 14, 1920], and correlating population dynamics with historical events [9, 12, 20, 2122].…”
Section: Introductionmentioning
confidence: 99%
“…While many of the studies inferring evolutionary rates for MTB reported support for a molecular clock [1011, 1314, 16, 18, 20, 22], some found a lack of clocklike structure [7, 1718], and others assumed a molecular clock without testing whether the data had a temporal structure [9, 12, 15, 19, 21]. In all studies where the calibration was based on the sampling time (tip-dating), the clock rate estimates spanned roughly an order of magnitude around 10 −7 nucleotide changes per site per year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current genome data show that the MTBC is comprised of the five human-adapted lineages representing M. tuberculosis sensu stricto (L1-4 and L7), two other humanadapted lineages traditionally referred to as M. africanum (L5-6) and at least nine animal-adapted lineages 6 . Africa is the only continent where all MTBC lineages are present, suggesting that the MTBC emerged from a common ancestor therein and then expanded to the rest of the world following human migrations 3,[7][8][9][10] . However, the genomic traits of this common ancestor and the region from which this expansion took place in Africa remain unknown.…”
mentioning
confidence: 99%